Fragment-Based Restricted Active Space Configuration Interaction with Second-Order Corrections Embedded in Periodic Hartree-Fock Wave Function - Lin, Hung-Hsuan; Maschio, Lorenzo; Kats, Daniel; Usvyat, Denis; Heine, Thomas (Journal of Chemical Theory and Computation, 2020)
We present a computational scheme for restricted-active-space configuration interaction (RASCI) calculations combined with second-order perturbation theory (RASCI-PT2) on a fragment of a periodic system embedded in the periodic Hartree-Fock (HF) wave function. This method allows one to calculate the electronic structure of localized strongly correlated features in crystals and surfaces. The scheme was implemented via an interface between the Cryscor and Q-Chem codes. To evaluate the performance of the embedding method, we explored dissociation of a fluorine atom from a lithium fluoride surface and partially fluorinated graphane layer. The results show that RASCI and RASCI-PT2 embedded in periodic HF are able to produce well-behaved potential energy surfaces and accurate dissociation energies.
CRIS-Team Scopus Importer:2022-04-14